Microestrutura, resistência mecânica e corrosão sob tensão em ligas de alumínio Al-0,3%Fe e Al-4%Cu processadas por extrusão em canal angular - Braga, Diogo Pedrino (2019)
Grain refinement is an important hardening mechanism in metallic alloys, notably when the grain size reaches the submicrometer scale. For this purpose, several techniques of Severe Plastic Deformation (SPD) have been employed, among which is the Equal-channel Angular Pressing (ECAP). However, the relation between grain size and corrosion resistance remains a controversial subject for most metallic materials. The aim of the present work is to evaluate the microstructure, the mechanical strength and the stress corrosion cracking (SCC) resistance of two ulfrafine grained aluminum alloys, AA1050 and Al-4%Cu, severely deformed by ECAP. Microstructure was analyzed by optical microscopy (OM), scanning (SEM) and transmission (TEM) electron microscopy, while the mechanical strength was evaluated through conventional hardness and tensile tests. Constant load and slow strain rate (SSR) tensile tests were carried out in an aqueous solution containing 3.5wt% of NaCl, in order to evaluate the SCC resistance of the alloys. After ECAP, OM and MEV revealed a significant grain size reduction in both alloys, with a fragmentation and redistribution of coarse second phase particles in the case of Al-4%Cu alloy. Hardness and tensile tests indicated a remarkable increase in the mechanical strength of the processed materials. In SSR tensile tests, with a relatively short time of exposure to the NaCl environment, CST was detected only in the Al-4% Cu alloy. In constant load tests, fractures occurred at stress levels lower than the yield stress, indicating CST susceptibility for long exposure times, in both alloys. In the absence of Cu particles (AA1050), no significant effects of ECAP processing were observed on the response to CST tests. In the case of Al-4% Cu alloy, it was found that the presence, as well as size and distribution, of the second phase particles affects the CST resistance, and that these factors can be modified, and possibly controlled, by means of ECAP processing.